2021
DOI: 10.3390/cancers13010151
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to KRASG12C Inhibitors

Abstract: KRAS is one of the most common human oncogenes, but concerted efforts to produce direct inhibitors have largely failed, earning KRAS the title of “undruggable”. Recent efforts to produce subtype specific inhibitors have been more successful, and several KRASG12C inhibitors have reached clinical trials, including adagrasib and sotorasib, which have shown early evidence of efficacy in patients. Lessons from other inhibitors of the RAS pathway suggest that the effect of these drugs will be limited in vivo by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 76 publications
1
87
0
3
Order By: Relevance
“…In agreement with previous reports [38], KRAS G12C is the most common KRAS variant and is currently targetable with clinically-approved covalently-bound inhibitors [39,40]. While clinical trials with various KRAS G12C inhibitors are in progress, data from patients and mouse models point to heterogeneous responses and therapeutic resistance as emerging issues [41]. Again, preclinical models, such as those described here, combined with clinical data, will be invaluable tools in understanding the mechanistic aspects of these issues but also to better stratify patients and possibly design improved inhibitors and therapeutic schemes.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with previous reports [38], KRAS G12C is the most common KRAS variant and is currently targetable with clinically-approved covalently-bound inhibitors [39,40]. While clinical trials with various KRAS G12C inhibitors are in progress, data from patients and mouse models point to heterogeneous responses and therapeutic resistance as emerging issues [41]. Again, preclinical models, such as those described here, combined with clinical data, will be invaluable tools in understanding the mechanistic aspects of these issues but also to better stratify patients and possibly design improved inhibitors and therapeutic schemes.…”
Section: Discussionsupporting
confidence: 89%
“…Emerging preclinical and clinical evidence shows that the biggest obstacle to KRAS-G12C inhibitor treatment is the inevitable emergence of drug resistance (Fig. 2) [31]. Although the problem of resistance to therapy is multifaceted, intercellular variability or intratumoral heterogeneity is considered to be the main factor leading to KRAS-G12C inhibitor resistance.…”
Section: Resistance To Kras-g12c Inhibitormentioning
confidence: 99%
“…However, therapeutic resistance to K-Ras G12C inhibition has been observed in preclinical tumor models and also in the clinic [ 273 , 274 , 275 ]. The PI3K pathway may be implicated in the resistance to K-Ras G12C inhibitors [ 276 ] as preclinical studies have shown failure to inactivate the PI3K signaling pathway after treatment with G12C inhibitors [ 274 , 277 , 278 ]. Importantly, combination of G12C and PI3K pathway inhibitors was effective in vitro and in vivo on models that are resistant to single-agent G12C inhibitor [ 274 ], or significantly improved antitumor activity of G12C inhibitors [ 277 , 279 ], which could be explained by a concomitant inhibition of p-ERK (due to G12C inhibition) and p-AKT [ 274 , 277 ].…”
Section: Ras–pi3k Interaction In Cancermentioning
confidence: 99%